Understanding the glioblastoma tumor microenvironment: leveraging the extracellular matrix to increase immunotherapy efficacy - Collado, Jimena; Boland, Lauren; Ahrendsen, Jared T.; Miska, Jason; Lee-Chang, Catalina (Frontiers in Immunology, 2024)
Glioblastoma (GBM) accounts for approximately half of all malignant brain tumors, and it remains lethal with a five-year survival of less than 10%. Despite the immense advancements in the field, it has managed to evade even the most promising therapeutics: immunotherapies. The main reason is the highly spatiotemporally heterogeneous and immunosuppressive GBM tumor microenvironment (TME). Accounting for this complex interplay of TME-driven immunosuppression is key to developing effective therapeutics. This review will explore the immunomodulatory role of the extracellular matrix (ECM) by establishing its contribution to the TME as a key mediator of immune responses in GBM. This relationship will help us elucidate therapeutic targets that can be leveraged to develop and deliver more effective immunotherapies.